2021
DOI: 10.3390/fi13100254
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of the COVID-19 Infodemic in Saudi Arabia

Abstract: COVID-19 has had broad disruptive effects on economies, healthcare systems, governments, societies, and individuals. Uncertainty concerning the scale of this crisis has given rise to countless rumors, hoaxes, and misinformation. Much of this type of conversation and misinformation about the pandemic now occurs online and in particular on social media platforms like Twitter. This study analysis incorporated a data-driven approach to map the contours of misinformation and contextualize the COVID-19 pandemic with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Similar results were observed in Saudi Arabia, where most misinformation is spread through WhatsApp. Of that, 46% was related to the pandemic [ 98 ]. Because of the widespread misinformation in Thailand, Mongkhon, Ruengorn, Awiphan, Thavorn, Hutton, Wongpakaran, Wongpakaran and Nochaiwong [ 99 ] revealed that those exposed for three or more hours in a day to misinformation were facing problems related to depression, anxiety, and insomnia.…”
Section: How Do Our Findings Compare With the Rest Of The World?mentioning
confidence: 99%
“…Similar results were observed in Saudi Arabia, where most misinformation is spread through WhatsApp. Of that, 46% was related to the pandemic [ 98 ]. Because of the widespread misinformation in Thailand, Mongkhon, Ruengorn, Awiphan, Thavorn, Hutton, Wongpakaran, Wongpakaran and Nochaiwong [ 99 ] revealed that those exposed for three or more hours in a day to misinformation were facing problems related to depression, anxiety, and insomnia.…”
Section: How Do Our Findings Compare With the Rest Of The World?mentioning
confidence: 99%
“…Nevertheless, there is an urgent need for an examination of the scale of Arabic COVID-19 disinformation. Arabic, for example, is currently Facebook’s third-most common language [ 7 ] and a language spoken by more than 400 million people [ 8 ] in countries with significant social media presence [ 9 ]. Hence, this study attempts to fill a gap in the literature by examining social media data retrieved from Twitter to better understand the main online discussions that revolve around COVID-19 misinformation.…”
Section: Introductionmentioning
confidence: 99%
“…These same videos were found circulating on messaging platforms, such as WhatsApp. As 1 of the world’s most popular messaging platforms and a significant source of COVID-19 misinformation [ 14 ], WhatsApp is suggested to be a vital source of rumors, with usage surpassing Twitter in Arab countries, such as Saudi Arabia [ 9 ]. Taken together, these studies provide an overview of the online ecosystem that allows Arabic COVID-19 disinformation to spread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization, the COVID-19 pandemic has generated an infodemic (i.e., an abundance of digital or physical information that includes false or misleading news and causes confusion, disinformation, insecurity, and mistrust in government officials and health authorities) [ 1 ]. Besides mass media, the rapid spread of information through the Internet and social media contributed significantly to this phenomenon and hindered accurate and reliable information [ 2 , 3 , 4 , 5 , 6 ]. A meta-analysis on mainstream and social media information sources reflected the infodemic’s expansion, revealing 2311 reports from 87 countries containing COVID-19 related information, of which 82% were false [ 7 ].…”
Section: Introductionmentioning
confidence: 99%